Impact of BMI z-score on left ventricular mechanics in adolescent girls - Justine Paysal; Justine Paysal; Etienne Merlin; Etienne Merlin; Emmanuelle Rochette; Emmanuelle Rochette; Daniel Terral; Stéphane Nottin (Frontiers Media S.A., 2023)
BackgroundAdolescent weight disorders ranging from anorexia nervosa (AN) to obesity (OB) can impact the heart by causing opposite alterations in its morphology, suggesting a direct impact of body mass index (BMI) on the heart. Cardiac function is relatively preserved as assessed by standard echocardiography. However, few studies have used 2D speckle-tracking echocardiography (2D-STE), which can detect subtle alterations of left ventricular (LV) function by evaluating deformations. This study aimed to assess the link between the BMI z-score of adolescent girls and myocardial function.MethodsNinety-one adolescent girls comprising 26 AN patients (age 14.6 ± 1.9 years), 28 OB patients (age 13.2 ± 1.4 years), and 37 controls (age 14.0 ± 2.0 years) underwent 2D-STE to assess LV morphology and myocardial global and regional deformations.ResultsThe BMI z-score of our population ranged from −4.6 to 5.2. LV morphological remodeling was significantly and positively correlated with the BMI z-score (R2 = 0.456, p < 0.0001 for LV mass). Global longitudinal strain (LS) and regional LS recorded at the mid and apical levels were significantly correlated with the BMI z-score (R2 = 0.196, p = 0.0001 and R2 = 0.274, p < 0.0001, respectively, for apical and medial LS). Circumferential strains and twisting mechanics were not correlated with the BMI z-score. Fibrinogen and systolic blood pressure were the main variables explaining the alteration of LS.ConclusionWe observed that the BMI z-score had an impact on LV mechanics, especially on medial and apical LS. Neither circumferential nor twisting mechanics were altered by the BMI z-score in adolescent girls.